Thermoelasticity, Superelasticity and Nanoscale Aspects of Structural Transformations in Shape Memory Alloys - Adiguzel, Osman (Springer Science and Business Media B.V., 2018)
Shape memory alloys have a peculiar property to return to a previously defined shape on heating after deformation in low temperature product phase region. These alloys take place in a class of functional materials due to the response to the variation of temperature, and they are used shape memory elements in a wide range of industry; in particular, they are used in the construction sector, aeronautical industry due to the energy dissipation properties. Shape memory effect is facilitated by martensitic transformation which is a solid state phase transformation and occurs in thermal manner in material on cooling from high temperature parent phase region. This transformation is governed by changes in the crystalline structure of the material. Thermal induced martensite occurs as martensite variants, twinned martensite, in self-accommodating manner on cooling from high temperature parent phase region. Mechanically deformation of these alloys in martensitic state proceeds through martensite variant reorientation by the detwinning process. Martensitic transition occurs as self-accommodated martensite with lattice invariant shears which occur in two opposite directions, <110>-type directions on the {110}-type plane of austenite matrix. In addition, shape memory alloys can exhibit another property called superelasticity performed in only mechanical manner. These alloys can be deformed just over austenite finish temperature, and recover the original shape on releasing the stress in superelastic manner. Copper based alloys exhibit this property in metastable ?-phase region, which has bcc-based structures at high temperature parent phase field and these structures martensiticaly turn into the layered complex structures following two ordered reactions on cooling. © 2018, Springer International Publishing AG.
1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017 -- 15 July 2017 through 19 July 2017 -- Sharm El Sheikh -- 254609
Keywords: Lattice invariant shear; Lattice twinning; Shape memory effect; Superelasticity; Thermoelasticity